Transcriptome analysis of the aquaporin AtPIP1;2 deficient line in Arabidopsis thaliana - Anastassia Boudichevskaia; Marlies Heckwolf; Lea Althaus; Ralf Kaldenhoff (Genomics Data, 2015)
Atmospheric CO2 impacts all aspects of plant development. It has changed in the past and is predicted to change further on. Studies on the response of crop plants to low and elevated CO2 concerning growth, productivity and physiological processes are intense. In contrast, the molecular mechanisms of cellular CO2 exchange are still under discussion. At the same time it becomes more and more accepted that carbon dioxide is transported across cellular biomembranes by CO2 conducting aquaporins. Our recent study (Boudichevskaia et al., 2015) demonstrates that the lack of a single gene product – aquaporin AtPIP1;2 – resulted in massive transcriptional reprogramming in Arabidopsis as a consequence of reduced tissue CO2 diffusion rates. Therefore, the transcriptome data of the aquaporin AtPIP1;2 deficient line can be used in the comparative expression analyses for better understanding the role of aquaporins with regard to CO2 and water transport in plants. Here we describe a gene expression dataset generated for three biological replicates per genotype on Affymetrix platform. We provide detailed methods and analysis on microarray data which has been deposited in Gene Expression Omnibus (GEO): GSE62167. Additionally, we provide the R code for data preprocessing and quality control.